(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Genotype-environment interaction was studied in seven genotypes of chickpea under four different cultural environments. Significant variation for genotype (G), environment (E) and G × E interactions were found for the characters days to maturity, plant height, pods/plant, seeds/plant, 100-seed weight and seed yield/plant. On the basis of stability parameters the genotypes Barichola-2, Barichola-3, Barichola-4, Barichola-7 and Barichola-8 could be considered stable for seed yield but suitable only under poor environments where no fertilizers were used. The genotype Barichola-1 was highly responsive but suitable for favorable environments only. DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17012